Voices from the retirees: Redefining quality of life in Sabah’s post-pandemic retirement landscape - Dzurizah Ibrahim; Jalihah Md Shah (IDEAS, 2024)
ABSTRACT This study explores into the intricate and subjective nature of quality of life, which evolves based on an individual’s interpretation and experiences. Existing indicators in Malaysia, intended for all societal strata, overlook the nuanced needs of specific age groups, employing a ‘one size fits all’ approach. Focusing on B40 public sector retirees in Sabah, this research explores the multifaceted meaning of quality of life through in-depth interviews with 62 retirees from five districts. The findings reveal that quality of life is underpinned by key themes: physical well-being, financial stability, social well-being, emotional well-being, health security, and religious values. These themes emphasize the self-sufficiency of B40 retirees, particularly in the post-pandemic era. The prevailing indicators fail to account for age-specific nuances, highlighting the need for Malaysia to prepare and support this demographic as the nation ages. Beyond contributing valuable perspectives, this study offers nuanced insights into the holistic well-being of retirees in Sabah, extending beyond existing literature. The study’s findings provide a basis for redefining quality of life in the context of B40 public sector retirees, emphasizing the importance of tailoring approaches to meet the distinct needs of this demographic in the evolving landscape of societal aging.